Conexões, conflitos e sociabilidades na territorialidade da escola e no ciberespaço - Mota, Rosália Monteiro (2017)
This research aimed to analyze the relationship between teachers and students, in the current context in which the new information and communication technologies affect the world of work, and also instrumentalize the teaching work and social relations. This case study anchored in qualitative research, raised questions in order to verify what would be prevalent or outstanding in the interactions between teachers and students in a public school of Elementary and Middle School in Belo Horizonte. In this study, the face-to-face and virtual connections, mediated by the use of social networks, indicated that the respect between these subjects was predominant, emphasizing that there is a scenario conducive to dialogue among all those who are part of the Institution. The school management prioritizes actions to maintain a good infrastructure of work, with electronic equipment available in the classroom, constant dialogue with teachers, students and their families, and administrative staff, workload for training, individual studies, interdisciplinar projects, correction and release of notes in electronic journals. Therefore, we could conclude that in this Institution interactions generated in classrooms and expanded to social networks are interconnected and influenced by different factors, such as the work structure, organizational climate and school management, important components in the direction of convergence, respect, and negotiations. The Institution was described by students and teachers as differentiated, because it develops practices aligned with the expectations of the teachers in the sense of care and respect, positively altering their expectations regarding the exercise of teaching, presenting satisfactory results in the aspect of learning and relationships, feelings that were convergent with the students' reports. However, they also pointed out problems that the school persistently and creatively tries to solve. Six teachers and fifty-eight students took part in this research. The Elementary and Middle School teachers participated through semi-structured interviews, and the students of the second year of High School through a questionnaire. In addition to the interviews and questionnaires we observed the routine of the Institution and some teaching activities. We talked to managers and examined records of occurrences. These incursions were fundamental to understand the feelings of teachers and students about the interactions and work developed in this school where being a teacher has a different meaning